Attenuation of urokinase activity during experimental ischaemia protects the cerebral barrier from damage through regulation of matrix metalloproteinase-2 and NAD(P)H oxidase - Rakkar, Kamini; Srivastava, Kirtiman; Bayraktutan, Ulvi (Wiley, 2014)
Ischaemic injury impairs the integrity of the blood–brain barrier (BBB). In this study, we investigated the molecular causes of this defect with regard to the putative correlations among NAD(P)H oxidase, plasminogen–plasmin system components, and matrix metalloproteinases. Hence, the activities of NAD(P)H oxidase, matrix metalloproteinase-2, urokinase-type plasminogen activator (uPA), and tissue-type plasminogen activator (tPA), and superoxide anion levels, were assessed in human brain microvascular endothelial cells (HBMECs) exposed to oxygen–glucose deprivation (OGD) alone or OGD followed by reperfusion (OGD + R). The integrity of an in vitro model of BBB comprising HBMECs and astrocytes was studied by measuring transendothelial electrical resistance and the paracellular flux of albumin. OGD with or without reperfusion (OGD ± R) radically perturbed barrier function while concurrently enhancing uPA, tPA and NAD(P)H oxidase activities and superoxide anion release in HBMECs. Pharmacological inactivation of NAD(P)H oxidase attenuated OGD ± R-mediated BBB damage through modulation of matrix metalloproteinase-2 and tPA, but not uPA activity. Overactivation of NAD(P)H oxidase in HBMECs via cDNA electroporation of its p22-phox subunit confirmed the involvement of tPA in oxidase-mediated BBB disruption. Interestingly, blockade of uPA or uPA receptor preserved normal BBB function by neutralizing both NAD(P)H oxidase and matrix metalloproteinase-2 activities. Hence, selective targeting of uPA after ischaemic strokes may protect cerebral barrier integrity and function by concomitantly attenuating basement membrane degradation and oxidative stress.